PENYELESAIAN SENGKETA TANAH ULAYAT ANTARA MASYARAKAT KENEGERIAN SIMANDOLAK DAN MASYARAKAT KENEGERIAN TERATAK AIR HITAM KABUPATEN KUANTAN SINGINGI - Urpi Rahma Weni; Firdaus '; Maryati Bachtiar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
The ulayat land dispute between the Kenegerian Simandolak community and the kenegerian Teratak Hitam Hitam society occurred in 2015 due to mutual claims and mutual claims of land rights on ulayat land on the second border of kenegerian, causing both kenegerian communities to attack each other with sharp weapons and air rifles causing injuries on both sides. Simandolak residents residing in Teratak Air Hitam Jaga were burned by the residents.The purpose of writing this thesis are: First, To know the factors that cause the occurrence of ulayat land disputes between the community Kenegerian Simandolak and Kenegerian people Teratak Air Hitam Kuantan Singingi Regency. Second, To know the process of settlement of land disputes between ulayat kenegerian Simandolak community and kenegerian people Teratak Air Hi tarn Kuantan Singingi, Third, obstacles in the settlement of land disputes ulayat between kenegerian Simandolak and kenegerian community Teratak Air Hitam Kuantan Singingi Regency.This type of research is sociological juridical research which means approach by looking in terms of legislation and the reality that occurred in the field.From the results of the study concluded, First, the causal factor of the ulayat land disputes between the people of Kenegerian Simandolak and the Kenegerian people of Teratak Air Hitam is the usage of ulayat land which is in Status Quo between two kenegerian, quarrels and the destruction of land that exist around ulayat land, kenegerian boundary is not clear . Second, the process of settling land disputes between the Communal of Kenandman Simandolak and Kenegerian Teratak Air Hitam is through consultation process and with the help of a third party or mediator but the result also can not satisfy each society. Third, the obstacles in the settlement of land disputes over the communal land between the Kenregerian Simandolak Community and the Kenegerian Teratak Hitam Hitam Community are the absence of an agreement to resolve the dispute between the two kenegerian, the village government can not solve because of the difficulty to disperse between two kenegerian, unsuccessful deliberations.Keyword: Dispute Resolution, Land Ulayat